Wild textiles grown, foraged, found - Fox, Alice (Batsford, 2022)
Alice Fox shows how to work with found, foraged, gathered and grown materials to create textile pieces. The book is packed with practical ideas for foraging - from weeds, dandelions and other plants useful for making cordage, or leaves that can be stitched, quilted and shaped into vessels, to grass, wool, plastics and mud. Other ideas for found materials include stones, shells and wood
Keywords: Sammeln; Pflanzen; Naturmaterial; Textilkunst; naturmaterialer; fibre; naturen; tekstiler; tekstilkunst; kunst; sankning